PENGARUH PENERAPAN SISTEM E-REGISTRATION,E-FILLING, DAN TRANSPARANSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK BADAN PADA KANTOR PELAYANAN PAJAK (KPP) PRATAMA MEDAN PETISAH DENGAN PEMAHAMAN INTERNET SEBAGAI VARIABEL MODERASI - Reni Sahfitri; Nurul Izzah Lubis (Jurnal Widya, 2024)
This research aims to determine the effect of implementing the E-registration, E- filling and Tax Transparency Systems on Taxpayer Compliance at the Pratama Medan Petisah Tax Service Office (KPP) with Internet Understanding as a Moderating Variable. The type of research used is quantitative research with associative methods. The data used is primary data in the form of a questionnaire, as well as secondary data in the form of data from the KPP Pratama Medan Petisah. The analysis techniques used are Multiple Linear Regression Analysis and Moderated Regression Analysis. The population in this research is all Corporate Taxpayers registered with KPP Pratama Medan Petisah and the sample is 100 people represented. The research results show that the variable implementing the e-registration and e-filling system has a positive and significant effect on corporate taxpayer compliance, while the variable implementing Tax Transparency does not have a positive and significant effect on taxpayer compliance. The internet understanding variable is able to moderate the implementation of the e-registration system on compliance. taxpayers, and the variable internet understanding is not able to moderate the implementation of the e-filling system and tax transparency on taxpayer compliance